Entrepreneurial Skill Needs of Sesame Farmers and Marketers in Katsina State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study was designed to investigate skill needs of sesame farmers and marketers in Katsina State. Descriptive survey design was adopted and 386 respondents were sampled from the population of registered sesame farmers and marketers in the state using multistage sampling technique. Data were collected on socioeconomic characteristics, skill needs, benefits and constraints using structured interview guide. Frequency counts, percentages, means, Ch-square and PPMC were employed in data analysis. Majority were young, male, married, Muslims, had Quranic education, large household size and operated small scale farms. Levels of skill needs for farmers and marketers were high. Major farmers’ skill needs were fertilizer application, pest/disease while skills to make goods and services available to customers at the right place and time, capture, negotiate/bargain, grad/sort/bag were among marketers’ major skill needs. Benefit levels were high for farmers and marketers. Inadequate facilities for training, education and training and cost of training were common constraints to farmers and marketers. Chi-square analysis revealed marital status as having significant association with farmers’ skill needs level while education significantly associated with both marketers and farmers’ skill needs levels. PPMC analysis indicated that farm size significantly correlated with farmers’ skill needs level just as significant correlation existed between benefit, constraint and farmers, marketers’ skill needs levels. Significant correlation existed between marketers’ years of experience and skill needs level. The t-test analysis result showed farmers and marketers in Katsina central senatorial district (KCSD) had significantly higher skill needs than their counterparts in the north senatorial district (NSD). Because the skill needs of both farmers and marketers were high coupled with low educational qualifications, government should develop those distinctive skill needs into training modules using local language for easy understanding and utilization.